Effectiveness of massage in the abdominal area to reduce infant colic - Castillo Ramírez, Marisol (2016)
Introduction. Infantile colic is a benign condition that may experience less than six months; however, although not life threatening, it can become a traumatic experience for parents and family, as well as being very annoying for the same infant.Method. For the development of this work practice research methodology based on evidence (PEBE) was used nurses, a clinical question was raised and electronic searches of MEDLINE, SIBDI, Google Scholar, PubMed, Cochrane Library Plus. After establishing the criteria for inclusion and exclusion and critical analysis, four documents to answer the clinical question he was selected.Results. No study directly answer the question, however, several studies confirms that massage reduces hours of crying, influences mood infant and promotes a change in attitude of parents to benign events colic infant.Conclusion. Infantile colic is one of the main problems that parents and children six months healthy infants face, so it is a query for health professionals who serve them. There is no scientific basis that abdominal massage alter some organic aspect the digestive tract, but there is evidence of changes in the behavior of infants, reduction of hours of crying and improving sleep, and improves attitude parents to the discomfort that infants may experience during periods of colic.